Early indicators of immunodeficiency in adults and children: protocols for screening for primary immunological defects - Sewell, W A C (Blackwell Science Inc, 2006)
SUMMARY: Early recognition of primary immunodeficiency is essential to reduce morbidity and mortality, and yet failure to recognize these conditions is still a major problem for clinicians around the world. The problem is that general practitioners, physicians and paediatricians lack familiarity with these rare disorders, and lack guidance regarding the appropriate use of immunological investigations. A working party from the European Society for Immunodeficiencies (ESID) has published screening protocols for these rare disorders, which aim to help select which tests should be done in which patients. The success of these proposals will depend on all immunologists disseminating this information in a format that is suitable for the busy generalist, who may not be familiar with these immunological tests and concepts. Laboratories should expect increasing requests for these screening investigations, and should make themselves familiar with these protocols so that appropriate second-line investigations can be arranged in a timely fashion. Speedy and effective communication between the laboratory and clinician is essential, and clinically interpreted reports are mandatory. Although these protocols are part of a screening process, their effectiveness in practice remains to be established, and further refinement will be required over time. The early involvement of the clinical immunologist in cases of suspected immunodeficiency is key.